Acetone Sensing Properties and Mechanism of SnO2 Thick-Films - Chen, Yanping; Qin, Hongwei; Cao, Yue; Zhang, Heng; Hu, Jifan (Sensors (Basel, Switzerland), 2018)
In the present work, we investigated the acetone sensing characteristics and mechanism of SnO2 thick-films through experiments and DFT calculations. SnO2 thick film annealed at 600 °C could sensitively detect acetone vapors. At the optimum operating temperature of 180 °C, the responses of the SnO2 sensor were 3.33, 3.94, 5.04, and 7.27 for 1, 3, 5, and 10 ppm acetone, respectively. The DFT calculation results show that the acetone molecule can be adsorbed on the five-fold-coordinated Sn and oxygen vacancy (VO) sites with O-down, with electrons transferring from acetone to the SnO2 (110) surface. The acetone molecule acts as a donor in these modes, which can explain why the resistance of SnO2 or n-type metal oxides decreased after the acetone molecules were introduced into the system. Molecular dynamics calculations show that acetone does not convert to other products during the simulation.